SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN - Wahdania (UNISAN JURNAL, 2024)
This research was conducted with the aim of; 1) describe the planning of academic supervision carried out by the principal of SMPI Integral Lukman Al Hakim 02 Batam , 2) describe the strategy for implementing academic supervision of the head of SMPI Integral Lukman Al Hakim 02 Batam , and 3) describe the implications of academic supervision of the head of SMPI Integral Lukman Al Hakim 02 Batam in improving the quality of learning at SMPI Integral Lukman Al Hakim 02 Batam . This study uses a descriptive qualitative approach, that is, researchers only describe, analyze phenomena, events and activities carried out related to academic supervision carried out by the head of SMPI Integral Lukman Al Hakim 02 Batam with data collection techniques through: (1) observation (2) in-depth interviews, and (3) documentation. As for the selection of research informants, using a purposive technique combined with snowball sampling. The data collected through the three techniques were then checked for validity by triangulation. Then analyzed by: (1) data reduction, (2) data presentation and (3) drawing conclusions. Conclusion: academic supervision is one way to increase teacher professionalism in planning, implementing the learning process and evaluating student learning outcomes in order to improve the quality of learning so that educational goals both locally and nationally can be achieved well. Keywords: Academic Supervision, Principal, and Quality of Learning